Penerapan Soft System Methodology pada Metode Penilaian Kerusakan Beton Secara Visual - Wiyanto, Henny (MEDIA KOMUNIKASI TEKNIK SIPIL, 2020)
Concrete damage on buildings can be interpreted as the presence of a change in the physical state of concrete. Damage can be in the form of change on the concrete surface or loss of concrete quality. To be able to identify the concrete damage condition on a building, inspection and assessment is required. Visual assessment is a method that can be a good first step to identifying the concrete damage condition on a building structure. Visual assessment is limited to concrete surface that can be accessed with visual senses. The goal of the research is to develop the concrete damage assessment method on a building visually that can be accepted by construction industry users in Indonesia with the Soft System Methodology (SSM) approach. Application of the SSM approach in this research uses the Root Definition component, CATWOE analysis, Rich Picture, and Conceptual Model. Result that is obtained from research, is the development concept for a visual method of building damage assessment, based on the seven steps according to SSM. Research results are in the form of a method that can identify and assess concrete damage while determining the concrete damage level on a building visually.